Līluḍī dharatī - Maḍiyā, Cunīlāla (Navabhārata Sāhitya Mandira, 2011)
Novel based on the life of rural family
Novel. - Reprint. Originally published: 1957. - Gujarati in Gujarati-Schr
Keywords: Rural families